Cognition et Hybridité. Le lecteur dans la zone grise - Arnaud Schmitt (Cahiers de Narratologie)
The aim of this article is to reassess the generic ambiguity inherent in autofiction from a cognitive point of view. Indeed, in the wake of the recent debate on autofiction, we would like to examine, not the nature, but the reception of these ambiguous texts. For instance, what is the cognitive basis of panfictionalism, the dominant approach when it comes to hybridity ? It is our contention that panfictionalism’s dismissal of generic frames remains unrealistic since the notion of frame (narrative schemas, cognitive types, perceptual habits…) is the necessary structure to get to grips with reality (even textual reality). For the “grey zone” to become tangible, the reader must suspend both belief and disbelief, but this indefinite position seems far removed from the reality of reading. What’s more, the exponents of hybridity overestimate our cognitive flexibility : there is every reason to believe that quite early in the process of reading a text, we opt for a genre or at least a specific horizon of expectation and, more often than not, stick to it.